Employee Motivation in Terms of Compensation, Leadership, Discipline, and Work Environment (Case Study at Tulung Health Center, Klaten Regency) - Hanung Sasmito Wibowo; Sudarwati Sudarwati; Istiatin Istiatin (UPN Veteran Yogyakarta, 2023)
This study aims to determine the effect of compensation, leadership, discipline, and work environment variables on employee motivation at the Tulung Health Center, Klaten Regency.This research method uses a quantitative descriptive research design. The population is all employees who work at the Tulung Health Center, Klaten Regency, totaling 44 people. The sampling technique used in this research is saturated sampling technique with a total sample of 44 respondents. Data collection using a questionnaire. This study uses the classical assumption analysis method, multiple linear regression test, model feasibility test (F test), hypothesis test (t test), and the coefficient of determination using SPSS 25. The results showed that (1) compensation has a significant effect on work motivation, (2) leadership has a significant effect on work motivation, (3) discipline has a negative effect on work motivation, and (4) work environment has an effect on employee motivation. Meanwhile, simultaneously, compensation, leadership, discipline, and work environment have a significant effect on employee motivation at the Tulung Health Center, Klaten Regency. Suggestions from this study, Tulung Health Center, Klaten Regency, to continue to improve compensation, leadership, discipline, and the existing work environment, so that it will also increase employee motivation and become better than before.